2018
DOI: 10.1088/1751-8121/aa8d24
|View full text |Cite
|
Sign up to set email alerts
|

Comment on ‘Two-state vector formalism and quantum interference’

Abstract: Hashmi et al (2016 J. Phys. A: Math. Theor. 49 345302) claimed that the approach to the past of a quantum particle introduced by Vaidman (2013 Phys. Rev. A 87 052104) has difficulties in certain examples and that it can even be refuted. Here I reply to their criticism showing that the approach provides a good explanation for all the examples they considered. It is fully consistent with standard quantum mechanics and provides a useful tool for analyzing interference experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 47 publications
0
4
2
Order By: Relevance
“…In our article [2] we have shown that the theory presented by the author of the comment runs into problems when applied to systems with multiple weak measurements, and that the trick used in the theory can be used to refute it. This is challenged in the preceding comment [1] claiming that we are mistaken in the analysis of certain examples discussed in our article [2]. However, the arguments presented in the comment [1] either endorse our results, or are inconsistent with the previously proposed theory [4].…”
contrasting
confidence: 85%
See 2 more Smart Citations
“…In our article [2] we have shown that the theory presented by the author of the comment runs into problems when applied to systems with multiple weak measurements, and that the trick used in the theory can be used to refute it. This is challenged in the preceding comment [1] claiming that we are mistaken in the analysis of certain examples discussed in our article [2]. However, the arguments presented in the comment [1] either endorse our results, or are inconsistent with the previously proposed theory [4].…”
contrasting
confidence: 85%
“…This is challenged in the preceding comment [1] claiming that we are mistaken in the analysis of certain examples discussed in our article [2]. However, the arguments presented in the comment [1] either endorse our results, or are inconsistent with the previously proposed theory [4]. With such inconsistencies the claim that we are mistaken in [2] remains insubstantial.…”
contrasting
confidence: 77%
See 1 more Smart Citation
“…Vaidman, together with his collaborators, performed an experiment demonstrating a surprising trace of the photons in nested interferometers [ 1 ] (see Figure 1 ). These results became the topic of a very large controversy [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…The faint trace will be on all parts of this line, but also in a separate loop disconnected from the line. The prediction of this closed loop, which does not start at the source and does not end at the detector, generated a hot discussion [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] which only intensified [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] after the first experiment with photons [22] confirmed discontinuous trajectories.…”
Section: Nested Mach-zehnder Interferometermentioning
confidence: 99%